Pinkalicious fashion fun - Kann, Victoria (New York, NY Harper, an imprint of HarperCollinsPublishers, 2016)
Pinkalicious and her friends create outfits using household items, like coffee filters and macaroni
Ages 4-8
2 13
Keywords: Pinkalicious -- (Fictitious character) -- Juvenile fiction; Fashion -- Fiction; Friendship -- Juvenile fiction; Friendship; JUVENILE FICTION / Humorous Stories; JUVENILE FICTION / Imagination & Play; JUVENILE FICTION / Reader - Beginner; JUVENILE FICTION / Readers / Beginner; JUVENILE FICTION / Social Themes / Friendship; Pink -- Fiction; Pink -- Juvenile fiction; Pink; Readers (Primary); Friendship -- Fiction; Pink -- Fiction; Readers (Primary.); Children's stories; Fiction; Juvenile works; Readers (Primary); Readers (Primary)